The effects of a 6-week pilates exercises on quality of life, depression, and musculoskeletal disorders in menopausal women - Arslan Kabasakal, Sema (The European Research Journal, 2025)
Objectives: This study examines the impact of a 6-week Pilates intervention on quality of life, depression, and musculoskeletal disorders in menopausal women. Methods: The sample comprised 13 menopausal women with a mean age of 59.45±11.52 years. Data collection was conducted using the World Health Organization Quality of Life-BREF (WHOQOL-BREF), the Beck Depression Inventory for Primary Care (BDI-PC), and the Cornell Musculoskeletal System Discomfort Questionnaire (CMSDQ). These instruments were administered at three intervals: baseline, following a 6-week non-intervention period, and after a subsequent 6-week Pilates program. Results: Within the scope of the study findings, after 6 weeks of Pilates, there was a significant increase in the participants' quality of life scores in the physical and psychological health domains (p